EFEITO DA RADIAÃ‡ÃƒO GAMA NO CONTRÃ”LE DA PODRIDÃƒO AZUL DOS FRUTOS CÃTRICOS - Ponte, J. JÃºlio da; Soave, Jaciro; Salgado, ClÃ©lio; Carvalho, Paulo C. T. de (REVISTA DE AGRICULTURA, 2016)
EFEITO DA RADIAÃ‡ÃƒO GAMA NO CONTRÃ”LE DA PODRIDÃƒO AZUL DOS FRUTOS CÃTRICOS